What behavior is important behavior? A systematic review of how wild and zoo-housed animals differ in their time-activity budgets - Kelly, Robert; Freeman, Marianne; Rose, Paul (Frontiers in Ethology, 2025)
Natural behavior performance in captive animals is traditionally utilized as a metric to establish welfare states, with an increase in natural behavior associated with positive welfare. Captive environments, including zoos strive to replicate ecologically relevant environments that promote species-specific, adaptive behavior performance. However, spatial restrictions and complex habitats required by some species create various challenges for zoo staff to implement management and husbandry practices to achieve this. Some species struggle to adapt and cope in captive environments, with increased abnormal behavior performance which may reduce welfare. Other species may adapt to captivity in novel ways, demonstrating flexibility in their behavior patterns without compromising welfare. However, research indicating positive behavioral flexibility in captive animals is sparse. The main aim of this review was to categorize animals as being fully behaviorally flexible, partially behaviorally flexible, or behaviorally inflexible. Effect sizes (Hedges’ g) were calculated to compare behavioral categories of animals in the wild and zoo, grouped by taxonomic Order (Testudines, Primates, Artiodactyla, Psittaciformes and Carnivora) and ecological traits to determine their level of behavioral flexibility. Effect sizes were also analyzed to determine behaviors suggestive of good welfare that were absent in zoo species. Despite variation across all groups, abnormal behavior was consistently highest in zoo animals, with reproductive and foraging behaviors most often compromised. Overall, complete positive behavioral flexibility was suggested in Testudines (potentially a result from temperature variation to maintain homeostasis), completely migratory species who are exposed to heterogenous landscapes when traveling long distances, and for a specific primate, the ring-tailed lemur (Lemur catta) potentially to improve resource access due to their terrestrial nature. All other groups evaluated demonstrated partial behavioral flexibility or behavioral inflexibility. Abnormal behavior prevalence and reduced foraging and reproductive behaviors in these groups suggests an inability to adapt to captivity. This necessitates more focused investigations that identify environmental features or aspects of managed environments that can meet a species’ needs in the zoo.